When Stakeholders Constrain or Enable Greenwashing: Evidence from Indonesia - Andy Dwiki Iranda; Etna Nur Afri Yuyetta (Politeknik Ganesha Medan, 2026)
This study examines the effect of stakeholder pressure on corporate greenwashing behavior from the perspectives of legitimacy theory and stakeholder theory. The research aims to analyze whether different forms of stakeholder pressure, namely government pressure, environmental pressure, consumer pressure, and creditor pressure, influence firms’ propensity to engage in greenwashing. The population of this study consists of publicly listed non-financial companies, observed over a multi-year period. Using purposive sampling, a total of 238 firm-year observations were obtained based on data availability and completeness of sustainability and financial disclosures. The study employs panel data regression with a random effects model, selected based on model specification tests. Given the presence of non-normal data distribution and autocorrelation, robust standard errors are applied to ensure reliable statistical inference, while diagnostic tests confirm the absence of heteroskedasticity and multicollinearity. The results indicate that government pressure and environmental pressure are negatively and significantly associated with greenwashing, suggesting that stronger regulatory oversight and environmental scrutiny reduce firms’ reliance on symbolic sustainability disclosures. In contrast, consumer pressure exhibits a positive and significant relationship with greenwashing, implying that market-driven sustainability demands may encourage symbolic reporting when verification mechanisms are weak. Creditor pressure shows a negative but statistically insignificant effect on greenwashing. These findings suggest that stakeholder pressure does not uniformly constrain greenwashing; instead, its effectiveness depends on the source and enforcement mechanism of the pressure. Overall, this study concludes that legitimacy-seeking behavior and strategic stakeholder management play a central role in shaping corporate greenwashing practices.